Ex uno plura : state constitutions and their political cultures - McHugh, James T., 1961- (Albany : State University of New York Press, 2003)
"State Constitutions have become increasingly important in light of recent trends in jurisprudence that favor decentralizing the American federal system. Ex Uno Plura uses a political culture approach to explore eight state constitutional traditions. McHugh argues that state jurisprudence is not merely a reflection of the process, values, and decisions found at the federal level, especially through the influence of the Fourteenth Amendment. A close examination of separate state constitutions, including their origins, sociopolitical cultures, and jurisprudence, reveals historically, culturally, and philosophically unique characteristics, each of which will contribute to the ongoing debate concerning American judicial federalism. The states included are Alaska, California, Georgia, Hawaii, Louisiana, Utah, Vermont, and Wyoming."--Jacket
Machine generated contents note: Ch. 1 Introduction. American Constitutionalism and Political Culture -- Ch. 2 Alaska. Frontier Autonomy -- Ch. 3 California. Diverse Microcosm -- Ch. 4 Georgia. Southern Republicanism -- Ch. 5 Hawaii. A Multi-Ethnic Heritage -- Ch. 6 Louisiana. Constitutional Patriarchy -- Ch. 7 Utah. A Liberal Theocracy -- Ch. 8 Vermont. A Republic Apart -- Ch. 9 Wyoming. Communitarian Ideal -- Ch. 10 Conclusion.
Includes bibliographical references (pages 255-317) and index.
Print version record.
English.
JSTOR
Keywords: Constitutional history -- United States -- States; Constitutional law -- United States -- States; State governments -- United States; Histoire constitutionnelle -- États-Unis -- États.; LAW -- Constitutional; LAW -- Public; Constitutional history -- U.S. states; Constitutional law -- U.S. states; State governments; United States